2010
DOI: 10.1364/boe.2.000026
|View full text |Cite
|
Sign up to set email alerts
|

The structural origin of second harmonic generation in fascia

Abstract: Fascia tissue is rich in collagen type I proteins and can be imaged by second harmonic generation (SHG) microscopy. While identifying the overall alignment of the collagen fibrils is evident from those images, the tridimensional structural origin for the observation of SHG signal is more complex than it apparently seems. Those images reveal that the noncentrosymmetric (piezoelectric) structures are distributed heterogeneously on spatial dimensions inferior to the resolution provided by the nonlinear optical mi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

5
30
0

Year Published

2011
2011
2023
2023

Publication Types

Select...
6
2

Relationship

3
5

Authors

Journals

citations
Cited by 46 publications
(35 citation statements)
references
References 41 publications
(47 reference statements)
5
30
0
Order By: Relevance
“…Parametric nonlinear microscopy of subwavelength structures may introduce distortions into the image that cannot always be predicted by models. For example, recent microscopy experiments using another parametric process, second harmonic generation (SHG), showed that image formation was not simply related to the concentration of the species being probed [8]. Similar distortions were previously discussed for backward direction-detected CARS signals [9].…”
Section: Introductionsupporting
confidence: 53%
“…Parametric nonlinear microscopy of subwavelength structures may introduce distortions into the image that cannot always be predicted by models. For example, recent microscopy experiments using another parametric process, second harmonic generation (SHG), showed that image formation was not simply related to the concentration of the species being probed [8]. Similar distortions were previously discussed for backward direction-detected CARS signals [9].…”
Section: Introductionsupporting
confidence: 53%
“…Collagen fibrils have a C 8 symmetry [21] and their c (2) tensor is characterized by three main elements in SHG microscopy, c zzz , c zxx and c xzx , where Z is the direction parallel to the fibrillar axis. All these tensor elements are achiral in nature [27,28] and can be probed using ISHG microscopy.…”
Section: Resultsmentioning
confidence: 99%
“…They are focussed by a 0.85 NA objective and collected by a 0.55 NA condenser. The use of a slightly lower NA condenser does not significantly alter SHG signal collection [21]. The reference beam interferes with the SHG generated in the sample.…”
Section: Methodsmentioning
confidence: 99%
“…30 A number of biological materials, such as cartilage, tendons, myosin-rich striated muscle, crystallized microtubules of mitotic spindles, and plant chloroplast, have been found capable of generating the second harmonic signal. [31][32][33][34][35][36] Thus, the identification of SHG sources within biological media is of primary importance for its further application in studies of the characteristics of biological organisms. The basis of SHG can be explained from molecular hyperpolarizability β, 19 given as…”
Section: Basis Of Shg Origin In Biological Mediamentioning
confidence: 99%